2016
DOI: 10.4137/cmt.s38232
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Benzodiazepine and Nonbenzodiazepine Agents, Ramelteon, Low-dose Doxepin, Suvorexant, and Selective Serotonin 5-HT2A Receptor Antagonists and Inverse Agonists on Sleep and Wakefulness

Abstract: 1 provides a classification system of sleep stages that comprises the following three different states: wakefulness (W), nonrapid eye movement (NREM) sleep, and rapid eye movement (REM) sleep. Relaxed W is characterized by an electroencephalogram (EEG) with alpha activity (8-12 Hz) intermixed with lower amplitude irregular beta waves (13-35 Hz), slow or rapid electrooculogram, eyelid blinks, a relatively high tonic electromyogram (EMG), and movement artifacts. NREM sleep is characterized by the following: stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Olanzapine has been reported to be associated with delirium prevention, 22 and multiple studies have indicated that olanzapine increases slow wave sleep and REM sleep. 55,56,66,67 A previous study reported that ramelteon had no effect on REM sleep (Table 5), 57 and in the present study, ramelteon did not show delirium-prevention effects. Consistent with this result, meta-analyses 40,41 and an RCT 42 have shown that ramelteon does not prevent delirium.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Olanzapine has been reported to be associated with delirium prevention, 22 and multiple studies have indicated that olanzapine increases slow wave sleep and REM sleep. 55,56,66,67 A previous study reported that ramelteon had no effect on REM sleep (Table 5), 57 and in the present study, ramelteon did not show delirium-prevention effects. Consistent with this result, meta-analyses 40,41 and an RCT 42 have shown that ramelteon does not prevent delirium.…”
Section: Discussionsupporting
confidence: 63%
“…13 Table 5 summarizes the sleep architecture during delirium and the effect of each sleepinducing medication on sleep. 17,[57][58][59] During delirium, rapid eye movement (REM) sleep and total sleep time (TST) are reduced 17,59 ; in particular, patients with serious disease have frequent awakenings and decreased REM sleep. 59 The reduction in REM sleep is attributed to increased inflammatory cytokine levels owing to DSWR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in advanced stages of the disease, concern about dependence should not prevent their prescription. Benzodiazepine can also alter the sleep architecture, increasing the N2 stage and decreasing the N3 and REM stages of sleep [67]. The Zolpidem augmentation of treatment with Venlafaxine and SSRI has shown to improve sleep and quality of life in breast cancer survivors [68].…”
Section: Discussionmentioning
confidence: 99%